Changes in aerobic performance in young football players in an annual training cycle - Sliwowski, R.; Rychlewski T.; Laurentowska, M.; Michalak, E.; Andrzejewski, M.; Wieczorek, A.; Jadczak, L. (Biology of Sport, 2011)
The aim of this study was to assess and compare the levels of aerobic performance of young football players in various periods of an annual training macrocycle. The study covered a group of fifteen 14-15-year-old football players of KKS Lech Poznan' S.A. The study was carried out on five dates in key moments of the time frame of the annual training cycle (the beginning and the end of the basic preparatory period, the end of the spring round of the starting period and the beginning and the end of the autumn round of the starting period). In order to establish the level of aerobic performance the subjects performed an exercise test with increasing intensity on a Woodway treadmill with a 5% elevation. The initial speed of the treadmill belt was 8 km/h and was increased every three minutes by 2 km/h until exhaustion. During the exercise test the following physiological indicators were recorded on an ongoing basis using the Cardio Pulmonary Exercise computer system (Medical Graphics Corporation, USA): VO2, VO2/kg, VE, VO2/HR, RQ, as well as the running speed (V) and the distance covered. The values of parameters obtained at the level of the ventilatory threshold and with maximum load were analysed. In order to test the significance of differences in mean values between five dates of tests, Friedman`s non-parametric analysis of variance (ANOVA) was used. The significance of differences between successive dates of tests was tested using post-hoc Friedman`s ANOVA test. The tests showed significant differences in aerobic performance of young footballers in individual periods of the annual training cycle. The most favourable changes in terms of exercise adaptation of the participants were noted after the basic preparatory period. Then statistically significant changes were noted in the majority of the tested physiological parameters both with maximum load (MAX) and at the level of the ventilatory threshold (VT). In starting periods, probably as a result of a shift in training emphasis towards special loads, their gradual regression was noted.